Biosorption OF Pb(II) and methylene blue onto chemically modified spent grated coconut (Cocos nucifera) / Khadijah Khalid - Khalid, Khadijah (2018)
Wastewater contaminated by lead (Pb(II)) heavy metal and methylene blue (MB) dye, and improper solid waste disposal of agro-based industries has been a major concern among the researchers. In addition, the uncertainty regarding the mechanism and process of biosorption involving the chemically modified biomaterials are also crucial that need to be investigated. This research investigated the application of three types of biosorbents derived from spent grated coconut (SGC) powder: hexane-washed (HSGC), sulphuric acid treated (SSGC) and xanthated spent grated coconut (XSGC) to adsorb two types of adsorbate cations namely Pb(II) and methylene blue (MB) dye from aqueous solutions. The biosorbents were characterised by spectroscopic and quantitative analyses. Different chemical treatments had successfully changed the physicochemical characteristics of all biosorbents such as the surface area, pore diameter, CHNOS content, pHslurry and pHPZC, light metal ions content and ash content. The morphology of the SSGC had become spongy-like whereas XSGC had formed a flake-like structure.